Agrochemistry Virtual Poster Competition (AVPC) 2022 E-Poster - UiTM, Unit Korporat Fakulti Perladangan & Agroteknologi (Faculty of Plantation and Agrotechnology, UiTM Kampus Jasin, 2022)
Agrochemistry Virtual Poster Competition 2022 is a platform to be formed for students / lecturers / staff to share creativity in applying the chemistry subjects learned in the world of Agrotechnology in the form of posters. This virtual poster competition takes place on 13 May 2022 and ends on 1 July 2022. This competition is an assessment of students in determining the level of understanding, creativity and group work for the subject of chemistry and being able to apply it to the field of Agrotechnology. The AVPC 2022 program takes place from May 13 to July 1, 2022. The program was officiated by the Dean of the Faculty of Plantation and Agrotechnology, namely Prof. Ts. Dr. Azhan Hashim @ Ismail. The program involves students from 3 faculties and HEP participating in AVPC 2022, namely the Faculty of Plantation and Agrotechnology (FPA), the Faculty of Applied Science (FSG), the Faculty of Education and Pre-Higher Education. This program involves 8 campuses namely Jasin Campus – 83, Perlis Campus – 35, Kuala Pilah Campus – 12, Shah Alam Campus – 7, Mukah Campus – 6, Puncak Alam Campus – 4, Kota Kinabalu Campus – 3, Jengka Campus – 2. Three categories are contested namely Pre Diploma, Diploma and Degree. To date, students from these programmes have shown remarkable achievements in academic performance and participations in national as well as international competitions.